2012
DOI: 10.1039/c2cp42496g
|View full text |Cite
|
Sign up to set email alerts
|

Surface-enhanced Raman spectroscopy studies of organophosphorous model molecules and pesticides

Abstract: This work reports the analytical application of surface-enhanced Raman spectroscopy (SERS) in the trace analysis of organophosphorous pesticides (trichlorfon and glyphosate) and model organophosphorous compounds (dimethyl methylphosphonate and o-ethyl methylphosphonothioate) bearing different functional groups. SERS measurements were carried out using Ag nanocubes with an edge square dimension of ca. 100 nm as substrates. Density functional theory (DFT) with the B3LYP functional was used for the optimization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 39 publications
(28 reference statements)
2
29
0
Order By: Relevance
“…The Raman spectral profile ( Figure S7) agrees to within a few wave numbers with previous reports [47,48]. The most intense signal appearing at 715 cm -1 , mainly assigned to the P-CH 3 stretching, has been used as Raman reference line.…”
Section: Sers Detection Of Dmmp In Gas Phasesupporting
confidence: 86%
“…The Raman spectral profile ( Figure S7) agrees to within a few wave numbers with previous reports [47,48]. The most intense signal appearing at 715 cm -1 , mainly assigned to the P-CH 3 stretching, has been used as Raman reference line.…”
Section: Sers Detection Of Dmmp In Gas Phasesupporting
confidence: 86%
“…SERS has been used for trace analyses and detection of residue of different organophosphorous pesticides and insecticides by employing various NSs, such as a solution of 100 nm Ag nanocubes or a Klarite Au‐coated SERS‐active substrate . For instance, Liu et al reported a detection of dimethoate at concentrations of 0.5 to 10 μg ml −1 acquired by confocal Raman microspectrometry with Klarite substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Concentrations of R6G as low as 1 nm have been measured, and a maximum enhancement higher than 10 5 has been achieved using Au-coated ZnO nanorods. [3] SERS has been used for trace analyses and detection of residue of different organophosphorous pesticides and insecticides [17][18][19][20][21][22] by employing various NSs, such as a solution of 100 nm Ag nanocubes [18] or a Klarite Au-coated SERS-active substrate. [19][20][21] For instance, Liu et al [19] reported a detection of dimethoate at concentrations of 0.5 to 10 μg ml −1 acquired by confocal Raman microspectrometry with Klarite substrate.…”
Section: Introductionmentioning
confidence: 99%
“…The Raman spectra of sarin and MPA were simulated based on density functional theory (DFT) by means of the Gaussian 09 software [44]. Figure 8(a) is the measured Raman spectrum for the pure MPA.…”
Section: Choice Of Sarin-simulated Agentmentioning
confidence: 99%